Balancing care and academic goals: how young adult carers navigate higher education - Villatte, Aude; Biaud, Marjorie; Piché, Geneviève; Habib, Rima; Vetri, Kelly (Frontiers in Education, 2025)
Young adult carers (YAC) often face unique challenges in higher education, yet their experiences remain underexplored. The objective of this study was to describe their experiences by comparing YAC with young adults who had an ill relative but were not carers (YANC) and with young adults without a sick relative (YAWSR). Participants included 436 students in higher education aged 18–30 years (122 YAC, 105 YANC and 209 YAWSR). They were asked to complete an online questionnaire about their school experience, the health of their loved ones, and the types of support potentially available to them. The school experience was analyzed using both objective (e.g., number of grades repeated and dropouts) and subjective indicators (i.e., self-report of academic, social, and emotional adjustment in the higher education context). The results of the study indicated that, while YAC did not self-rate their academic and social adjustment more negatively, they reported experiencing more emotional difficulties and a less linear academic trajectory in comparison to their peers in the other two groups. These findings highlight the importance of providing more support for YAC to improve their school experience in higher education, mental health, and future adult life.